FROM THE ENLIGHTENMENT SCIENTISTS MAHMUDHOJA BEHBUDII (American Journal of Pedagogical and Educational Research, 2024)
This article analyzes Mahmudhoja Behbudi, Jadidism, the emergence of the first Jadid schools, and the activities of enlightened scientists.